A visual based target detection and tracking system (II) - Tan, Augustine Peng Soon. (2010)
The main objective of this project is to design and create a visual sensor system and it’s Graphics User Interface (GUI). 4 cameras were used for this visual sensor system to detect and identify the different robots from the images captured. There are 2 major portions in this project, the calibration process and the extraction process.